PENGARUH ATRIBUT PRODUK, PROMOSI PENJUALAN, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN YANG DIMEDIASI OLEH PREFERENSI DAN MINAT BELI KONSUMEN (Studi pada Kosmetik Sariayu Marta Tilaar di Semarang) - Gama Rossa Romadhoningrum; Suryono Budi Santoso (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of product attributes, sales promotions, and word of mouth on interest in purchasing Sariayu cosmetics, analyze the effect of product attributes, sales promotions, and word of mouth on consumer preferences related to Sariayu cosmetics, and analyze the influence of buying interest and consumer preferences. on the decision to purchase Sariayu cosmetics. This study was conducted using a survey method to the consumers of Sariayu Marta Tilaar cosmetics in Semarang. The sample in this study amounted to 193 people. The sampling technique used is purposive sampling. Research data were collected using a questionnaire. Data analysis was performed using Multiple Regression Analysis Techniques, t test, F test, and Sobel test. The results showed that 1) There was a positive influence of product attributes, sales promotions, and word of mouth on the purchasing decisions of Sariayu cosmetics. 2) There was a positive influence of product attributes, sales promotions, and word of mouth on the purchase intention of Sariayu cosmetics. 3) There was a positive influence of product attributes, sales promotions, and word of mouth on consumer preferences for Sariayu cosmetics, 4) There was an influence positive buying interest and consumer preferences on the purchasing decisions of Sariayu cosmetics. The results also show that buying interest mediates the effect of product attributes, sales promotion, and word of mouth on Sariayu cosmetic purchasing decisions. Consumer preferences mediate the effect of product attributes and sales promotions on Sariayu cosmetic purchasing decisions, and consumer preferences do not mediate the influence of word of mouth on Sariayu cosmetic purchasing decisions